Propozycja modyfikacji dowolnego indeksu wyznaczającego liczbę skupień w zbiorze danych - Korzeniewski, Jerzy (A Proposal of Modification of Arbitrary Data Set Cluster Number Index, 2007)
In the paper a proposal of the modification of an arbitrary data set cluster number index is given. The idea of the modification is to obtain a lower bound of the number of clusters in a data set through analysing the distribution of pairwise distances. The modification was tested on 216 data sets from Euclidean spaces with the grouping done by the k-means method. The indices modified were the Rousseeuw silhouette index, the Krzanowski-Lai index, the Caliński-Harabasz index and the Hartigan index.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 314-320